2011
DOI: 10.1179/joc.2011.23.2.59
|View full text |Cite
|
Sign up to set email alerts
|

Albumin-Bound Paclitaxel: The Benefit of This New Formulation in the Treatment of Various Cancers

Abstract: Paclitaxel and docetaxel are established as the standards of care, either as monotherapy or in combination with other cytotoxic agents in metastasic breast cancer. In order to improve the efficiency of solvent-based paclitaxel and to overcome its drawbacks in terms of safety, a solvent-free formulation has been developed. This work is a review of the albumin-bound paclitaxel data relative to its pharmacodynamic and pharmacokinetic profiles, its therapeutic efficiency and its safety of use. The activity of albu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 45 publications
0
42
0
Order By: Relevance
“…No hypersensitivity reactions were reported in several phase i, ii, and iii studies that used this agent 28,[62][63][64] , and administration of nab-paclitaxel was well tolerated in 5 patients who had previously experienced hypersensitivity reactions to paclitaxel 65 . However, one phase iii study indicated that nab-paclitaxel can cause hypersensitivity reactions 28 .…”
Section: 34mentioning
confidence: 99%
See 1 more Smart Citation
“…No hypersensitivity reactions were reported in several phase i, ii, and iii studies that used this agent 28,[62][63][64] , and administration of nab-paclitaxel was well tolerated in 5 patients who had previously experienced hypersensitivity reactions to paclitaxel 65 . However, one phase iii study indicated that nab-paclitaxel can cause hypersensitivity reactions 28 .…”
Section: 34mentioning
confidence: 99%
“…Substitution of Therapy A new formulation of nanoparticle albumin-bound paclitaxel (nab-paclitaxel) avoids the use of Kolliphor as a vehicle, and thus premedication is not required 61,62 . No hypersensitivity reactions were reported in several phase i, ii, and iii studies that used this agent 28,[62][63][64] , and administration of nab-paclitaxel was well tolerated in 5 patients who had previously experienced hypersensitivity reactions to paclitaxel 65 .…”
Section: 34mentioning
confidence: 99%
“…Recently, this strategy of combination between cyclodextrins and bioadhesive nanoparticles has demonstrated effectiveness in improving significantly the oral bioavailability of paclitaxel [102]. This anticancer drug is widely used in clinic for the treatment of several carcinomas including breast [103], advanced ovarian [104], non small cell lung [105] and colon [106]. By the oral route, it shows a very low bioavailability, which is caused by several factors.…”
Section: Figurementioning
confidence: 99%
“…Clinical trials have shown that Abraxane was better tolerated and more effective against melanoma than was free PTX. 44,45 However, a recent report showed that poly(gamma-L-glutamylglutamine)-PTX was more effective in reducing the growth of xenografted B16 melanoma cells than was Abraxane and had less side effects.…”
Section: Common Nanoparticles Used In Melanoma Treatmentmentioning
confidence: 99%